Increased Frequency of Dermatological Diseases in Parkinson's Patients - Seemab Khan; Nighat Fatima; Asma Bano; Farooq Khan; Faiza Khan; Saira Isa (Life and Science)
Objective: To determine the frequency of seborrheic dermatitis, bullous pemphigoid, rosacea, and melanoma among the patients diagnosed with Parkinson Disease. Study Design: Cross sectional study. Place and Duration of Study: The study was carried out at Dermatology Department of Bakhtawar Amin Trust th th Teaching Hospital Multan from 13 May to 13 October 2020. Materials and Methods: A total of 80 patients of Parkinson disease were evaluated for skin disorders. Disease severity was confirmed through Hoehn Yahr staging criteria (H-Y stage). Skin characteristics and disease diagnosis was made through finding sebum production levels, hot/cold flush test, immunofluorescence and biopsy evaluation for seborrheic dermatitis, rosacea, bullous pemphigoid, and melanoma, respectively. The test results were compared with control subject. Chi square test and student t-test were used to find the significance of results. P < 0.05 will be statistically significant. Results: Out of 80, 44 patients were positive for skin disorders. The frequency of seborrheic dermatitis was 31.2% and was quite high as compared to control group that was 25% whereas rosacea, bullous pemphigoid and melanoma was found in 15%, 6.2% and 2.5% patients and in control group they were 11.2%, 2.5% and 1.0% respectively. To detect the significant difference between quantitative variables of test and control group, chi square was used and student t-test was used to compare the qualitative variables. P < 0.05 will be statistically significant. Conclusion: Skin disorders are highly prevalent among Parkinson's patients than control population.